Perancangan E-Commerce untuk Bakery & Cake dengan Opencart: Optimalisasi Fitur Promosi di Kecamatan Hiliran Gumanti - Rahmi, Miftahur; Annas, Firdaus; Wulandari, Mely; Nur Khaliq, Muhammad; Samsinar, Siti (JOVISHE : Journal of Visionary Sharia Economy, 2024)
The purpose of this study is to create an e-commerce bakery and cake in Hiliran Gumanti District that uses the OpenCart platform and optimizes promotional features. Qualitative research and research and development (R&D) use the 4 D approach (Define, Design, Develop, and Disseminate). In the Define stage, a needs analysis is conducted by asking customers and business owners to find obstacles in conventional marketing. In the design stage, an OpenCart-based e-commerce is designed to include promotional features such as discounts, coupons, loyalty programs, and special offers. In the development stage, the e-commerce is installed and tested to ensure that the promotional features work well and are easy to use. Furthermore, the disseminate stage includes deploying the platform and teaching customers and bakery business owners to use it. Research shows that optimized promotional features in e-commerce can increase business appeal, expand market reach, and increase sales. Businesses can more easily manage transactions, inventory, and marketing campaigns with OpenCart. By utilizing e-commerce technology as an innovative way to increase competitiveness, this study provides a practical contribution to the development of MSMEs in the culinary sector, especially in the Hiliran Gumanti area. By using the 4D approach, e-commerce development becomes more structured, in line with business needs, and easy to adopt.